Design, CFD analysis, and experimental validation of a NACA 4415 ducted hydrokinetic turbine for low-velocity river applications - Ma. Leona Maye B. Pepito; Kent B. Ignalig; Ian Keanu E. Becoy; Keith John D. Tadifa; John Kenno P. Lumasag (Researcher and Lecturer Society, 2026)
Hydrokinetic turbines represent a promising solution for renewable energy generation in low-velocity rivers where conventional hydropower systems are not technically or economically feasible. Despite increasing interest in ducted hydrokinetic turbines, experimental validation of turbines employing the NACA 4415 airfoil under low-flow river conditions remains limited. This study presents the design, computational fluid dynamics (CFD) analysis, and experimental validation of a horizontal-axis ducted hydrokinetic turbine using the NACA 4415 airfoil, specifically optimized for low-velocity river applications. Numerical simulations and field experiments were conducted for water velocities ranging from 0.89 to 1.03 m/s to evaluate turbine performance in terms of rotational speed, torque, power output, and power coefficient. The results indicate that the four-bladed ducted turbine achieved a maximum experimental power output of 67 W at a flow velocity of 1.03 m/s, corresponding to a power coefficient of 0.32. The diffuser-augmented configuration enhanced flow acceleration and rotational speed compared to theoretical predictions and numerical simulations, although performance discrepancies were observed due to hydrodynamic losses and mechanical inefficiencies. Overall, the findings demonstrate the feasibility and effectiveness of NACA 4415 ducted hydrokinetic turbines for decentralized renewable energy generation in low-flow river environments, contributing valuable experimental data for the development and optimization of small-scale hydrokinetic systems.